1998
DOI: 10.1111/j.2044-8309.1998.tb01175.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Just an ordinary Australian’: Self‐categorization and the discursive construction of facticity in ‘new racist’ political rhetoric

Abstract: Australia has recently witnessed the resurgence of what has been termed the ‘race debate’. The apparently high levels of popular support from ‘ordinary’ Australians for MP Pauline Hanson's contentious views on immigration, Australia's indigenous peoples and her foreign relations have been a major theme of this debate. This paper employs the framework of discursive psychology to examine, in her maiden speech to Parliament, the way in which Pauline Hanson's political rhetoric is precisely constructed in order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 8 publications
5
107
0
Order By: Relevance
“…However, studies on ' new racism' have shown that the idea of fundamental and inherent cultural differences is also used to exclude and abnormalize ethnic minority groups (e.g. Barker, 1981;Hopkins et al, 1997;Rapley, 1998;Taguieff, 1988;Wieviorka, 1995). Hence, the effect of cultural essentialism is not self-evident but seems to depend on how it is used and the context where it appears.…”
mentioning
confidence: 99%
“…However, studies on ' new racism' have shown that the idea of fundamental and inherent cultural differences is also used to exclude and abnormalize ethnic minority groups (e.g. Barker, 1981;Hopkins et al, 1997;Rapley, 1998;Taguieff, 1988;Wieviorka, 1995). Hence, the effect of cultural essentialism is not self-evident but seems to depend on how it is used and the context where it appears.…”
mentioning
confidence: 99%
“…Here she uses active voicing (an emblematic quotation, Potter, 1996;Wooffitt, 1992) typical of her past experiences with men in football. Positioning it in past experiences increases the factualness of the claim (Rapley, 1997) and Belinda's credibility as a witness (a special category for building "truthfulness", Potter, 1996). The plural active voicing -deploying the general category of "men" and how "they view it" -also makes it easy to hear the account as "a general experience of a range of people" (Potter, 1996, p.161, emphasis in original).…”
Section: Managing Resistance To the Privileging Of Masculinist Discoumentioning
confidence: 99%
“…Rapley (1998) examined facticity in relation to the racism and dogmatism of an Australian politician's speech and the discursive devices she used in establishing such facticity. The way in which the contents of the speech are constructed as indisputable fact are analysed along with the way in which offensive and defensive rhetoric are employed.…”
Section: Review Of European Studiesmentioning
confidence: 99%